The effects of subchronic intake of magnesium hydrocarbonate-rich mineral water on body weight and cardiovascular variables in rats with streptozotocin: Induced diabetes - Đuric Dragan M.; Milošević Filip; Todorović Dušan; Živković Vladimir; Srejović Ivan; Jakovljević Vladimir; Stojiljković Miloš P.; Škrbić Ranko; Dragičević-Cvjetković Dragana; Vučković Sonja (Scripta Medica, 2022)
Background/Aim: Optimal intake of magnesium minerals is essential in maintaining the coordinated physiological functions of cells, tissues and organs. The importance of this element is reflected in the fact that it is the fourth most abundant cation in the human body, participating as a cofactor in more than three hundred enzymatic reactions. Its presence is necessary for the proper functioning of a number of vital functions, such as glycaemic control, the work of the heart and the vascular system and it can potentially play a role in the regulation of body weight. Aim of this study was to investigate the effects of subchronic intake of magnesium hydrocarbonate-rich water on changes in body weight, organ weight and cardiovascular variables in rats with streptozotocin-induced diabetes. Methods: Wistar rats (n = 28) were divided into 4 groups: two control groups, on tap water (TW-C, n = 7) and magnesium hydrocarbonate-rich water (MW-C, n = 7); and two experimental groups with streptozotocin-induced diabetes, on tap water (TW-DM, n = 7) and magnesium hydrocarbonate-rich water (MW-DM, n = 7). The values of body weight, organ weight and cardiovascular parameters were compared after 6 weeks between control groups of rats on subchronic treatment with tap water (TW-C) and magnesium hydrocarbonate-rich water (MW-C) and between groups with streptozotocin-induced diabetes on tap water (TW-DM) and with magnesium hydrocarbonate-rich water (MW-DM). Results: By comparing the values of cardiovascular parameters between groups, significant (p < 0.05) positive effects of magnesium hydrocarbonate-rich water were registered on the values of systolic and pulse blood pressure in diabetic rats fed with magnesium hydrocarbonate-rich water (MW-DM) compared to those fed with tap water (TW-DM). In contrast, no significant effect of magnesium hydrocarbonate on changes in body weight and organ weight was observed. Conclusion: Based on the results, the beneficial effects of magnesium hydrocarbonate-rich water in the regulation of blood pressure can be clearly observed. Potential effects on other cardiovascular variables and body weight and organ weight should be further investigated.